Singapore's transboundary haze pollution act : silver bullet or silver lining - Raman Letchumanan (2015)
Singapore's Transboundary Haze Pollution Act came into effect on 25 September 2014. The impending dry season in the coming months will be the first test of its effectiveness in curbing transboundary haze pollution.